EFEKTIVITAS MODEL READING GUIDE DALAM MENINGKATKAN HASIL BELAJAR DAN KARAKTER SISWA SDN 143 INPRES LEKO KABUPAATEN MAROS - Rimawati, Rimawati; Ashari Hamzah, Rahma; Erniati, Erniati (JURNAL PENDIDIKAN DASAR, 2025)
Abstract: This study examines the effectiveness of the reading guide model in improving Indonesian language learning outcomes and strengthening the character of fourth-grade students at SDN 143 Inpres Leko, Maros Regency. The background of the study is the low academic achievement, where only 30.76% of 26 students achieved the KKTP. With a pre-experimental design of one group pretest-posttest and observation, test, and documentation instruments, the analysis results showed a significant increase in the average score after the implementation of the model, evidenced by the Wilcoxon test (sig. <0.05). In addition, there was a development in student character, especially in the aspects of discipline, responsibility, and cooperation. These findings confirm that the reading guide model is effective in improving learning outcomes while shaping student character. Keywords: reading guide, learning outcomes, character   Abstrak: Penelitian ini mengkaji efektivitas model reading guide dalam meningkatkan hasil belajar bahasa Indonesia dan penguatan karakter siswa kelas IV SDN 143 Inpres Leko, Kabupaten Maros. Latar belakang penelitian adalah rendahnya capaian akademik, di mana hanya 30,76% dari 26 siswa yang mencapai KKTP. Dengan desain pra-eksperimen one group pretest-posttest serta instrumen observasi, tes, dan dokumentasi, hasil analisis menunjukkan adanya peningkatan signifikan pada nilai rata-rata setelah penerapan model, dibuktikan melalui uji Wilcoxon (sig. < 0,05). Selain itu, terjadi perkembangan karakter siswa, khususnya pada aspek disiplin, tanggung jawab, dan kerja sama. Temuan ini menegaskan bahwa model reading guide efektif dalam meningkatkan hasil belajar sekaligus membentuk karakter siswa. Kata Kunci: reading guide, hasil belajar, karakter